STABILIZATION OF GALUNGGUNG SAND WITH CUT - BACK BITUMEN - Indrianto, Tri
The eruption of Galunggung mountain in 1982 resulted in the deposition of great amounts of material in the surrounding area. This created considerable concern, principally because of the likelihood of "mudflows" during the wet season. Efforts were immediately made to remove the material and the Government instructed that where, possible, it should be used as a construction material. The objective of the research described in this thesis was to determine if Galunggung sand can be stabilized to meet specific criteria for road base material using a cold-mix combination of cut-back bitumen, clayey silt and water. For this purpose, several combinations of clayey silt and water were investigated. The test results indicate that, over the range investigated, increasing the clayey silt content of the mixture results in increased stability. Increase in water content results in increased stability for all levels of clayey silt content. All of the mixes investigated meet criteria fixed by THE ASPHALT INSTITUTE (1975) for sand-bitumen mixtures; the majority meet the more demanding criteria established by HARRIS et al (1983). A satisfactory mix is obtained with 5 percent residual bitumen, 9 percent clayey silt and 6 percent water.